Evaluation of a Ventilating System for Indoor Air Quality and Smoke Exhaust during Fire inside an Underground Parking. Issue 1 (May 2021) - Bode, F; Sandu, M; Năstase, I; Calotă, R
Abstract: Together with the modern urbanization development, the number of underground cars parkings has grown significantly. They are provided with ventilation systems to evacuate the cars emissions and with smoke exhaust systems which intervene in case of fire. Generally, the same exhaust system is used to evacuate the emissions and the smoke from a potential fire even if the working parameters are not the same for both scenarios. The paper deals with a case study regarding an underground parking designed for 15 cars. Numerical simulations using CFD tools have been performed to establish the CO concentrations. The results prove that the CO concentration limits are exceeded due to the positioning of the exhaust grills. In case of a fire, the temperatures are still high. The conclusion is that CFD simulations are needed for this type of ventilating systems design and that only following the regulation prescriptions is not enough in case of fires.